Metro Cebu: A Metropolitan Area in Need of Coordinative Body - Glenda R. Gonzales (Philippine Institute for Development Studies (PIDS), 2004)
Urbanization and rapid increase in population in Metro Cebu brought about increased demand for basic services and infrastructure. The creation of the Metro Cebu Development Council comprising of the four (4) cities and six (6) municipalities in the eastern part of the Cebu Province, as an organizational structure, attempts to address these problems. However, services that require areas larger than a local jurisdiction for cost-effective provisioning like water supply, garbage disposal and solid waste management are still a problem. The same is true for services like public health and basic education whose benefits and costs accrue to non-residents of a local jurisdiction. Financial sustainability of the MCDC is at also risk because it is donor-driven or its budget is tied with the funds coming from its partner agencies. A more permanent and solid body that will look closely at the various needs of Metro Cebu for a more efficient delivery of basic services is much needed. Also a body in terms of financial capability, like a metropolitan development authority, should be established to address the current and future urbanization and population growth problems.
Keywords: 330; metropolitan arrangements; Metro Cebu; Metro Cebu Development Council; Urbanisierung; Bevölkerungswachstum; Großstadt; Kommunalverwaltung; Kommunale Versorgungswirtschaft; Kommunale Dienstleistung; Kommunale Infrastruktur; Infrastrukturinvestition; Cebu; Philippinen